2019
DOI: 10.1111/mcn.12816
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain and newborn anthropometric outcomes in rural Bangladesh

Abstract: Low gestational weight gain (GWG) is a known predictor of fetal growth restriction in higher income countries, but there is little information on this association in lower income countries. Our objective is to describe the association between GWG and birth outcomes among pregnant women in rural Bangladesh. Pregnant women were identified in a community‐based programme and enrolled into the study at an average of 13 weeks' gestation (n = 4,011). Maternal weight and height were measured at enrolment, maternal wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
6
19
0
Order By: Relevance
“…We also found that an inadequate rate of weight gain was most frequent among underweight women, and excessive weight gain was common among overweight women. These findings are in line with that of other studies in low- as well as high-income countries [ 6 , 7 , 8 , 9 , 41 ] and highlight the importance of starting pregnancy with a normal body weight and preconception counseling.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We also found that an inadequate rate of weight gain was most frequent among underweight women, and excessive weight gain was common among overweight women. These findings are in line with that of other studies in low- as well as high-income countries [ 6 , 7 , 8 , 9 , 41 ] and highlight the importance of starting pregnancy with a normal body weight and preconception counseling.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective chart analysis of data from 29,861 women in 25 U.S. hospitals found higher odds of macrosomia among women with rates of GWG above IOM recommendations (AOR = 2.66, 95% CI: 2.03, 3.48) but did not find any association with weight gain below the recommendations [ 5 ]. In another recent study in two rural sub-districts in northwest Bangladesh, compared to women with inadequate GWG during the second and third trimester, women who gained weight at a rate within the IOM guidelines had a lower risk of delivering LBW and SGA infants [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,27] The associations of GWG with birth length and head circumference, however, have rarely been evaluated. [28–30] Inadequate GWG in this study was positively associated with the risk of stunting and microcephaly at birth. A longitudinal study of 670 pregnant women in The Gambia similarly found that greater GWG at any level was positively associated with head circumference, but only greater GWG above a threshold of 0.5 SD of conditional weight gain (i.e.…”
Section: Discussionmentioning
confidence: 71%